Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

2x-(3x-1) divided by 4 = 4

Sagot :

1)   2x-(3x-1)       ---------------------------------- = 4                         4

2)  4* 
2x-(3x-1)
---------------------------- =4*4
            4                          the 4's get cancelled..
3) 2x-(3x-1)= 16
4) 2x-3x+1=16
5) 2x-3x = 16-1
6) -x = 15
 7) x=-15
Hope this helps you!!! =')

[tex]\frac{2x - (3x - 1)}{4} = 4 \\\frac{2x + 3x + 1}{4} = 4 \\\frac{5x + 1}{4} = 4 \\\frac{5x}{4} + \frac{1}{4} = 4 \\\frac{4}{5} * \frac{5x}{4} = 3\frac{3}{4} * \frac{4}{5} \\x = 3[/tex]